Review paper Association between dermatological diseases and pathological changes in the gastrointestinal tract - Chmiel, Katarzyna; Krela-Kaźmierczak, Iwona; Łykowska-Szuber, Liliana; Niśkiewicz, Izabela; Linke, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
A lot of primary dermatologic diseases, such as mastocytosis and epidermolysis bullosa, have a tendency to manifest their symptoms in the digestive tract. Malignant melanoma is one of the most common neoplasms that form metastases in the intestines. Almost all patients with systemic scleroderma have symptoms resulting from a pathological process that takes place in the esophagus. On the other hand, the skin is the area of extraintestinal manifestation of various gastrointestinal pathologies. The strongest linkage is observed between dermatitis herpetiformis, pyoderma gangrenosum, erythema nodosum and intestinal inflammation. Bazex syndrome, acanthosis nigricans and the sign of Leser-Trélat are paraneoplastic syndromes that suggest existence of gastrointestinal cancers, that is why thorough knowledge of their clinical characteristic is extremely important.